Evasão de um curso técnico de enfermagem: percepção de estudantes não concluintes - Oliveira, Amanda Aparecida Camargo de (2017)
In Brazil each and of four students that enter in the elementary school one theirs to throw up the school before of to complete the last series. The School flight is a complicate social phenomenon, multidimensional, expression of a collective problem with consequences not only academic, but also social and economic. Aim: This study has the purpose to identify the reasons of flight for students in a state nursing technical course, in the interior of São Paulo, to characterize the demographic and work profile of the not finished students, and to propose actions that may helper to reduce evasion. Method: This is a descriptive, documentary research with a qualitative-quantitative approach. The study included 18 students who evaded in the first semester of 2014. The sample included students from four groups who presented in the year in question the percentage of 18.66% of avoidance. An oral interview conducted, recorded in audio, guided by questions about the reasons for avoidance and ways of avoiding them. In addition, participants replied to a form with socio-demographic and work data. The subject of the interviews organized according to the reference of the Discourse of the Collective Subject for the analysis and interpretation of these data the subject analysis used modality thematic analysis. Sociodemographic dice analyzed according to the frequency of inconstant. Results: showed that the participants were mostly women, aged between 18 and 35 years, children of parents with low level of education, since most didn’t attend high school, and 50% of families live with income of one to three wages Minimum. The causes of evasion identified by the interviewees categorized into individual (maternity, change of address, illness in the family), environmental (need to work, financial difficulties, schedules incompatibility) and academic (dissatisfaction with the choice of course, with the work of Completion of course, unsatisfactory academic result). The environmental factors predominated, the incompatibility of schedules as the main cause of evasion. This agent is entail to the difficulty of to harmonize academic activities and the world of work and is due to the need to work to make up the family budget. Participants suggested welcoming actions (listening to students, active search), academic measures (diversifying schedules, improving CBT), and measures to support students in financial difficulties as ways to avoid circumvention. Listening to the student, in order to "be attentive" to their difficulties and confrontations, especially in the learning teaching process was proposed by two participants and considered by the school team to receive the return of the results as the most important action in the fight against evasion, by its preventive and humanized character. It is concluded that the student's access to and permanence in the course involves not only pedagogical questions but also measures that consider the context and the singularity of the student, as well as require co-responsibility of all the professionals involved